Microfinance systems : designing quality financial services for the poor - Wright, Graham A. N. (London ; New York : Zed Books; Dhaka : University Press, New York : Distributed in the USA exclusively by St Martin's Press, 2000)
The book discusses the many problems and challenges facing micro-finance, and offers experienced, down-to-earth recommendations for practitioners. It also advocated the power of microfinance to the contribution of poverty alleviation.
Includes bibliographical references (p. [267]-276) and index.
nmn 11/06/13
Loans
Keywords: Microfinance; Financial services industry; Financial services - Poor; Microfinance system